Enhancing group‐based internet obesity treatment: A pilot RCT comparing video and text‐based chat - Delia S. West; M. Stansbury; R. A. Krukowski; J. Harvey (Wiley, 2019)
Summary Objective Internet delivery of behavioural weight control interventions offers potential for broad geographic reach and accessibility, but weight losses online fall short of those produced with the same programme delivered in‐person. This pilot study examined feasibility and preliminary efficacy of a video‐based platform for delivering weekly chat as part of a 6‐month, 24‐session online group behavioural weight control programme compared with the established text‐based format, which has produced the best online weight losses to date. Method Women with obesity (N = 32) were randomized to either (a) weekly video group chat sessions and provided with a cellular‐enabled scale (Video) or (b) Text‐based weekly chat sessions and given a digital scale (Text) and followed for 6 months to determine weight loss and treatment engagement. Results Women randomized to the ideo condition lost more weight than those in the Text condition (−5.0 ± 6.0% vs. −3.0 ± 4.1%, respectively) at 6 months, although the difference was not statistically significant. However, women in the Video condition had significantly greater treatment engagement, with greater self‐monitoring and website utilization than those in the Text condition. Conclusions Videoconference delivery of group‐based online weight control accompanied by a cellular‐connected scale may promote greater treatment engagement and weight loss than text‐based chat. A larger, adequately powered study is warranted to determine which elements drive these enhanced treatment outcomes.